Design And Development Of An RS232-Based ROV Controller System. - Md. Zain, Zainah; Ahmad, R. Badlishah; Arshad, Mohd. Rizal (2004)

(untitled)
The overall design of an underwater robot which includes the design of electro-mechanical components and the control circuit diagrams are introduced.